Zatory płatnicze a bankructwo przedsiębiorstw. Propozycja rozwiązań systemowych na podstawie wykorzystania rachunku bankowego - Pastusiak, Radosław (Delay Payments and Corporate Bankruptcy. General Solutions Supported by Banking Current Account, 2008)
Receivables are normal element of trade. A problem arises when a company delays payments. Payment delays are caused by the lack of liquidity. In some cases the lack of liquidity leads to corporate bankruptcy. Declaring bankruptcy in Poland can be a very long and complicated process, and there is no guarantee that the all receivables will be received from the debtor. Using current procedures like: insurance, information data or factoring, companies can secure risk of default. A better solution would be using current bank account which should be an obligatory method of invoice payment. In case of lack of money in the current account, the bank starts procedures the firm to solve its problems or sends a notice of bankruptcy. Thanks to these procedures, financially insufficient companies would be eliminated from the market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 419-425